2017
DOI: 10.1016/j.trb.2016.11.004
|View full text |Cite
|
Sign up to set email alerts
|

A statistical method for estimating predictable differences between daily traffic flow profiles

Abstract: This is a repository copy of A statistical method for estimating predictable differences between daily traffic flow profiles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(33 citation statements)
references
References 64 publications
0
33
0
Order By: Relevance
“…Statistical methods have long been used to predict traffic flow. The typical statistical methods include the autoregressive integrated moving average (ARIMA) method [12], [13] and the B-spline method [14]. Machine learning methods have more recently been widely used to predict passenger flow and traffic variables.…”
Section: Related Literature Review a Methods Of Passenger Flow Prmentioning
confidence: 99%
“…Statistical methods have long been used to predict traffic flow. The typical statistical methods include the autoregressive integrated moving average (ARIMA) method [12], [13] and the B-spline method [14]. Machine learning methods have more recently been widely used to predict passenger flow and traffic variables.…”
Section: Related Literature Review a Methods Of Passenger Flow Prmentioning
confidence: 99%
“…To show the contribution of each variable to the final clustering results, the F test was conducted based on ANOVA analysis [29]. Due to that the queue length and delay are represented by interval data in the proposed method, a binary linear regression was conducted first in order to measure the contribution of the interval data.…”
Section: Contribution Of Variablesmentioning
confidence: 99%
“…With TTR properly measured, researchers could focus on diagnosis of travel time unreliability causes ( 24 27 ). Kwon et al applied an empirical corridor-level method to divide the contributions of multiple non-recurrent events, such as weather, incident, work zone, and special events on travel time variation and found that incident has the highest contribution among non-recurrent events ( 24 ).…”
Section: Literature Reviewmentioning
confidence: 99%